Peran Moderasi Profitabilitas dalam Pengaruh CSR dan GCG terhadap Nilai Perusahaan pada Perusahaan Tambang di Indonesia - Deni Triamanda; Helma Malini; Uray Ndaru Mustika; Anggraini Syahputri (eCo-Fin, 2025)
This study examines the effect of Corporate Social Responsibility (CSR) and Good Corporate Governance (GCG) on firm value, with Return on Assets (ROA) as a moderating variable. The research was conducted on mining sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period, using purposive sampling techniques with a total of 120 observations (firm-year). Data analysis was performed using panel data regression with the Random Effect Model approach and interaction testing through Moderated Regression Analysis (MRA). The results show that CSR and GCG have no significant effect on firm value (proxied by Price to Book Value/PBV). Meanwhile, ROA has a negative and significant effect on firm value. In addition, the interactions of CSR_ROA and GCG_ROA are also not significant, indicating that profitability does not moderate the relationship between CSR and GCG on firm value. These findings indicate that in the mining sector, profitability, CSR, and GCG are not yet strong indicators influencing investor perception. Profitability without a clear earnings utilization strategy can reduce market confidence, and CSR or GCG implementation that is merely formal does not enhance firm value.